2012
DOI: 10.1002/ana.22692
|View full text |Cite
|
Sign up to set email alerts
|

Demyelination affects temporal aspects of perception: An optic neuritis study

Abstract: Conduction velocity in the visual pathways correlated closely with dynamic visual functions, implicating the need for rapid transmission of visual input to perceive motion. Motion perception level may serve as a tool to assess the magnitude of myelination in the visual pathways. The constancy across patients may serve as a baseline to assess the efficacy of currently developing neuroprotective and regenerative therapeutic strategies, targeting myelination in the central nervous system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
58
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 29 publications
7
58
0
Order By: Relevance
“…The present data are also consistent with previous findings showing impaired motion [19,30,31] or achromatic stimuli [20] processing, thus also suggesting a magnocellular deficit among ON patients that appeared to have full ophthalmologic recovery. Magnocellular deficits have been proposed to represent a behavioural correlate of demyelination in ON patients [31,32].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present data are also consistent with previous findings showing impaired motion [19,30,31] or achromatic stimuli [20] processing, thus also suggesting a magnocellular deficit among ON patients that appeared to have full ophthalmologic recovery. Magnocellular deficits have been proposed to represent a behavioural correlate of demyelination in ON patients [31,32].…”
Section: Discussionsupporting
confidence: 93%
“…Magnocellular deficits have been proposed to represent a behavioural correlate of demyelination in ON patients [31,32]. However, it is interesting to note that in ON patients, the deficit in processing LSF only occurs in terms of error rate and not in terms of reaction time.…”
Section: Discussionmentioning
confidence: 99%
“…Using the OFM protocol, we have demonstrated a sustained deficit in the affected eyes of ON patients, evident even 12 months following the optic neuritis attack, while standard visual functions had recovered 8 . Furthermore, impaired performance was associated with delayed conductions (delayed P100, reflecting demyelination) and improvement in motion perception was correlated with shortening of conduction rates (reflecting remyelination; linear least squares regression with calculation of the correlation coefficient F=27.3; p=0.0005; r=-0.87) 9 .…”
Section: Dynamic Visual Tests May Be Used As Markers Of Demyelinationmentioning
confidence: 99%
“…The correlation between OFM scores and VEP (P100) latency values indicate that OFM may not only identify, but also quantify the demyelinative damage. The correlation between improvement in the OFM protocol and shortening of VEP latencies along time 9 suggest that the OFM protocol may also sensitively quantify remyelination.…”
mentioning
confidence: 99%
“…Despite exhibiting normal detection abilities in their visual field, patients with optic neuritis are impaired in motion detection and temporal processing tasks [19][20][21]. Longitudinal studies showed that perception of stationary stimuli, as presented in perimetry, recovers fast after the optic neuritis episode, but deficits in dynamical aspects of perception persist [20,21].…”
Section: Introductionmentioning
confidence: 99%